Decentralisation and Economic Growth - Part 1: How Fiscal Federalism Affects Long-Term Development - Blöchliger, Hansjörg (OECD Working Papers on Fiscal Federalism, 2013)
Intergovernmental fiscal frameworks usually reflect fundamental societal choices and history and are not foremost geared towards achieving economic policy objectives. Yet, like most institutional arrangements, fiscal relations affect the behaviour of firms, households and governments and thereby economic activity. This paper presents empirical research on the potential effects of fiscal decentralisation on a set of outcomes such as GDP, productivity, public investment and school performance. The results can be summarised as follows: decentralisation, as measured by revenue or spending shares, is positively associated with GDP per capita levels. The impact seems to be stronger for revenue decentralisation than for spending decentralisation. Decentralisation is strongly and positively associated with educational outcomes as measured by international student assessments (PISA). While educational functions can be delegated either to sub-central governments (SCG) or to schools, the results suggest that both strategies appear to be equally beneficial for educational performance. Finally, investment in physical and - especially - human capital as a share of general government spending is significantly higher in more decentralised countries